210k views
5 votes
Simplify the expression 43 + 2(3 − 2).

14
16
66
68

User Podkova
by
4.6k points

2 Answers

3 votes

Multiply the bracket by 2

43+2(3-2)

Follow PEMDAS

P= parentheses

E=exponents

M= multiplication

A= Addition

S= Subtraction

43+2(3-2)

43+6-2

Add next

49-4

45

There is no choice for 45 even though it is the right answer.

Answer is 45

User Viktor Ilienko
by
5.4k points
2 votes

Answer:

45.

Explanation:

Work out the parentheses first.

43 + 2(3 − 2)

= 43 + 2 * 1

= 45.

User Manik Biradar
by
4.6k points